Creating sustainable democracy in Africa - an African supranational body for the effective supervision of elections in Africa - Quashigah, Edward Kofi (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2008.